2016
DOI: 10.1590/s1678-9946201658026
|View full text |Cite
|
Sign up to set email alerts
|

CD19 LYMPHOCYTE PROLIFERATION INDUCED BY Bifidobacterium animalis subsp. lactis IN C57BL/6 MICE EXPERIMENTALLY INFECTED WITH Toxoplasma gondii

Abstract: SUMMARYToxoplasmosis is frequently acquired through the oral route by the ingestion of cysts or oocysts of Toxoplasma gondii. Once ingested, the parasites penetrate the intestinal epithelial cells and rapidly disseminate to all organs in the host. During T. gondii infection, the intestinal microbiota plays an important role in stimulating a protective immune response against the parasite. In this sense the use of probiotics is worthy of note since they are live microorganisms that have beneficial effects on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Toxoplasma infection in experimental animals has been shown to alter several aspects of intestinal immunity (Cohen and Denkers 2015a,b). Conversely, the intestinal microflora may be one factor controlling the immune response to Toxoplasma in the intestinal tract and hence host resistance to Toxoplasma infection (Ribeiro et al, 2016). Acute Toxoplasma infection has also been shown to change the microbiome of experimentally infected mice.…”
Section: Toxoplasma and Intestinal Inflammationmentioning
confidence: 99%
“…Toxoplasma infection in experimental animals has been shown to alter several aspects of intestinal immunity (Cohen and Denkers 2015a,b). Conversely, the intestinal microflora may be one factor controlling the immune response to Toxoplasma in the intestinal tract and hence host resistance to Toxoplasma infection (Ribeiro et al, 2016). Acute Toxoplasma infection has also been shown to change the microbiome of experimentally infected mice.…”
Section: Toxoplasma and Intestinal Inflammationmentioning
confidence: 99%
“…Recent studies have revealed that the gut microbiota plays an important role in the regulation of hematopoiesis. Compared with specific pathogen-free (SPF) mice, germ-free mice have smaller hematopoietic stem and progenitor cell (HSPC) populations (Ribeiro et al, 2016). Similarly, oral antibiotics have suppressive effects on hematopoiesis including anemia by depleting intestinal bacteria (Josefsdottir et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The milk microbiome reflects thousands of years of human evolution, and neonatal exposure to these pioneering bacteria is essential for immunological maturation (54). Highly relevant to hospitalized infants, commensal bacteria stimulate antibody production (55), synthesize vitamins (56), protect against pathogens (57,58), and stimulate intestinal angiogenesis (59).…”
Section: Infant Microbiotamentioning
confidence: 99%